2012
DOI: 10.1155/2012/278050
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of sE-Selectin Levels 2–24 Months following Gestational Diabetes Is Associated with Early Cardiometabolic Risk in Nondiabetic Women

Abstract: Objective. We hypothesised that the endothelial dysfunction is associated with early glucose dysregulation and/or atherosclerosis risk factors in nondiabetic women with a previous history of gestational diabetes (pGDM). Material/Methods. Anthropometric parameters, glucose regulation (OGTT), insulin resistance (HOMA), lipids, biomarkers of endothelial dysfunction, and inflammation were evaluated in 85 women with pGDM and in 40 controls 2–24 months postpartum. Results. The pGDM group consisted of 67% normoglycem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Therefore, we agree with Chao et al, that from an epidemiological point of view parameters of endothelial dysfunction might contribute only little for diabetes prediction as compared to traditional risk factors including fasting glucose, body composition and clinical risk factors (as was shown by the authors in a large sample of postmenopausal women) [ 35 ]. This was also reflected by another recent report, where sE-selectin levels correlated with components of the metabolic syndrome, but however, were not independently related to abnormal glucose regulation early after delivery [ 36 ]. We have previously examined several risk factors for diabetes progression by using data of the present study and have identified parameters of disturbed carbohydrate metabolism (e.g.…”
Section: Discussionmentioning
confidence: 54%
“…Therefore, we agree with Chao et al, that from an epidemiological point of view parameters of endothelial dysfunction might contribute only little for diabetes prediction as compared to traditional risk factors including fasting glucose, body composition and clinical risk factors (as was shown by the authors in a large sample of postmenopausal women) [ 35 ]. This was also reflected by another recent report, where sE-selectin levels correlated with components of the metabolic syndrome, but however, were not independently related to abnormal glucose regulation early after delivery [ 36 ]. We have previously examined several risk factors for diabetes progression by using data of the present study and have identified parameters of disturbed carbohydrate metabolism (e.g.…”
Section: Discussionmentioning
confidence: 54%
“…In this view, the authors have proposed the necessity of new markers to be used to study the effect of GDM on cardiovascular risk during follow-up [29, 30]. Sokup et al [31] showed that the TG/HDL-C ratio, an early marker of endothelial dysfunction and CV risk, was higher in GDM women one year after the pregnancy, as compared to controls. In this context, of particular relevance is the association found in the present study between, respectively, APOA5 -1131 T>C and MC4R rs17782313 with 3rd trimester HDL-C in GDM women.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the TG/HDL-C ratio has been identified as a surrogate cardio-metabolic risk marker that may predict adverse CV outcome in hypertensive subjects (22). Sokup et al recently reported that TG, HDL-C, and the TG/HDL-C ratio were elevated in GDM women at around one year after the index pregnancy, and may represent an early marker of endothelial dysfunction and CV risk [ 39 ]. They further found that this atherogenic lipid profile in non-diabetic women with a history of GDM was independent of both HOMA-IR and BMI.…”
Section: Discussionmentioning
confidence: 99%